Mass Transport Complexes on a Cenozoic paleo-shelf edge, Gippsland basin, southeastern Australia. (December 2018) - O'Brien, P.E.; Mitchell, C.H.; Nguyen, D.; Langford, R.P.
Abstract: The Southern Platform of the Gippsland Basin of southeastern Australia contains a mixed carbonate-clastic succession deposited on the outer continental shelf in water depths of 50–200 m. Seismic geometry indicates the presence of likely carbonate build-ups formed in deeper water near the north-eastern edge of the Southern Platform by bryozoan mounds which pass to the northeast into distal bottom set deposits in shelf edge clinoforms. Mass Transport Complexes (MTCs) developed along the paleo-shelf edge and basin bounding faults through repeated failure from the Late Oligocene to the Mid Miocene. Two distinct Mass Transport Complexes are present. The Sailfish MTC affects a zone 7 km wide along the paleo-shelf edge in the SE of the area and features slumped paleo-shelf masses with listric faulting and toe thrusts in places. Some inversion of slump-related structures indicates continued movement after an initial failure event. The Devilfish MTC is up to 32 km wide and consists of a zone of extension which passes downslope into a broad zone of compressional structures which die out downslope without the development of a clear emergent slump mass or a terminal structure. Stratigraphic relationships suggest that it formed progressively by creep from the Late Oligocene to the Late Miocene. The difference in deformation styles between the two MTCs can be explained by proximity to major basin forming faults. The Devilfish MTC formed where the paleo–shelf edge sat adjacent to an underlying fault which juxtaposes deeper basin fill sediments against basement. This geometry provided abundant pore water to weaken the overlying sediments which failed under differential loading imposed by shelf edge build ups to form the MTC, possibly triggered by repeated earthquakes. Devilfish MTC differs from mass transport deposit described in the literature in comprising an extensional headwall zone and a main body affected by compressional structures which then die out downslope, probably because of thickening of the section and a return to normal porewater pressures basin-ward. This type of MTC could be termed "Frontally Diffuse" in contrast to the recognised Frontally Emergent and Frontally Confined MTC terminations. Graphical abstract: Highlights: Eocene-Oligocene carbonate-clastic sediments on the southern flank of the Gippsland Basin feature stacked paleo-shelf edges. Mass Transport Complexes (MTCs) formed along these paleo-shelf edges from the Oligocene to the Late Miocene. These MTCs include some where deformation dies out downslope. We term these features Frontally Diffuse MTCs. MTC characteristics on the Southern Terrace of the Gippsland Basin are controlled by major basin structures. The Frontally Diffuse MTCs form a previously unrecognised end member in the classification of Mass Movement deposits.